Genome evolution in the allotetraploid frog Xenopus laevis - Session, Adam M. (Nature, 2016)
To explore the origins and consequences of tetraploidy in the African clawed frog, we sequenced the Xenopus laevis genome and compared it to the related diploid X. tropicalis genome. We demonstrate the allotetraploid origin of X. laevis by partitioning its genome into two homeologous subgenomes, marked by distinct families of “fossil” transposable elements. Based on the activity of these elements and the age of hundreds of unitary pseudogenes, we estimate that the two diploid progenitor species diverged ~34 million years ago (Mya) and combined to form an allotetraploid ~17–18 Mya. 56% of all genes are retained in two homeologous copies. Protein function, gene expression, and the amount of flanking conserved sequence all correlate with retention rates. The subgenomes have evolved asymmetrically, with one chromosome set more often preserving the ancestral state and the other experiencing more gene loss, deletion, rearrangement, and reduced gene expression.